SOCIO-ECONOMIC AND ENVIRONMENTAL IMPACT OF PARTICIPATORY WATERSHED MANAGEMENT PROGRAMME AT KOTHALE VILLAGE - Ramakant, Mundada; Ambiket, Gadkar; U.S., Ansari (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Any living thing is not suffer without water. Now a day there is lac of water tan demand of water.The problem of water is arising since thousands of years.Watershed can be defined as the drainage basin of a catchment area of a particular stream or river including glaciers. Watershed development is used to the conservation, regeneration and judicious utilization of the entire resources such as land, water and vegetative, animal and human within a particular watershed. The watershed development is nothing but percolate and stores the flowing rain water, due to that increase in economy of village and overall development of village. Village will be stable or suffer even if there is drought condition. Due to watershed management increase agriculture standard and to bring the barren land under cultivation. Yield of crops can be increased due to proper use of available water. We take different crop pattern due to that we use limited water. Thechemical and physical properties of water to determine properties. This includes survey about progress and model preparation of case study place. Study of watershed development project increase economy of villagers, increase in price and productivity of land. Increase in physical and chemical properties of water and soil.